TEKNIK PEMASANGAN MESIN UNTUK KAPAL PERIKANAN - Habibie, Ied; Ahmad, Muchtar; Nofrizal, Nofrizal (Jurnal Perikanan dan Kelautan, 2010)
The integration of engine into the wooden boat needs good knowledge ofeffective engine installation technique. Otherwise, the function of engine will notharmonic with the aims to move the boat properly to be optimum. The effectivenessof engine installation has link to engine foundation, the position of propeller axispoint at the height of keel and the stern. Two systems of engine installation, whichhave experimented and observed its effectiveness; first the lobe point of propelleraxis at the horizontal position just on the middle of the height of the “L” pillarbetween the keel and bosom of stern ceiling. Secondly, the propeller horizontal axishole in the point at the mid-height of keel-end and the ceiling of stern as the propellerposition. The result found that the first technique causes the power of engine weakeras compare to the second one; whilst the keel and engine fundation have to bemodified so that the position of engine foundation can be well on horizontal line,which caused change of the keel strength or the boat strength will be lesser. Hence,by mean the propeller axis lobe point at the mid-height between keel-end and thestern bosom found to be effective as the function of engine as power to move the boatworks better with less engine noise and vibration than the other technique.